The impact of physical activity on adolescent mental health status: the mediating effect of school adaptation - Zhang, Menghan; Gu, Chenguang; Zeng, Hui; Yi, Xiangren (Frontiers in Psychology, 2025)
ObjectiveThis study was designed to examine the mental health status of Chinese adolescents, investigate the effects of adolescent physical activity on mental health status, and verify the mediating effect of school adaptation.MethodsA survey and analysis were conducted on 9,701 high school students in Shandong Province using the Physical Activity Questionnaire for Adolescents (PAQ-A), the School Social Behavior Scale-2 (SSBS-2), and the Symptom Checklist-90 (SCL-90) self-rating scale. The overall status of adolescent mental health was analyzed, regression modeling along with structural equation modeling was used to test whether school adaptation played a mediating role.ResultsThe structural equation model was validated as a good fit (GFI = 0.950, RMSEA = 0.048, CFI = 0.972, NFI = 0.970, SRMR = 0.077). Physical activity was significantly and positively correlated with mental health status (β = −0.691, p < 0.001), school adaptation (β = 1.153, p < 0.001), and school adaptation was significantly and positively correlated with mental health status (β = −0.287, p < 0.001). The direct effect of physical activity on mental health status was 0.011 and the indirect effect of physical activity on school adaptation and school adaptation on mental health status was 0.024.ConclusionPhysical activity was positively related to mental health status, with physical activity significantly and positively predicting mental health status; school adaptation was significantly and positively related to physical activity and mental health status, with school adaptation mediating between physical activity and mental health status.